Enhancing first aid knowledge for students at SDN Mojorejo 2 Sragen - Irma Mustika Sari; Erika Dewi Noorratri (Community Empowerment, 2024)
Elementary education is a time when children actively interact with their friends. Play interactions sometimes carry a risk of injury for elementary school children. The national incidence of injuries at school is 5.4%. The highest prevalence rate of injury occurs in school children, namely 13%, and in the age range of 5-14 years. Inappropriate first aid can have detrimental effects on the victim. The aim of this community service activity is to increase students' knowledge of first aid for minor injuries. The method of implementing the service is through counseling using video media and training in treating minor injuries. After providing counseling and training on treating minor injuries to students at SDN Mojorejo II Sragen, they showed an increase in "good" knowledge of 74.0%, then the level of "sufficient" knowledge was 20.8%, and the level of "poor" knowledge was 5.2%. It can be concluded that the community service activities are going well, and it is hoped that students will be able to apply the knowledge about treating minor injuries obtained in the family and community environment.